Titulação em fluxo-batelada com detecção baseada em filmes digitais para determinação da acidez total de vinhos tintos - Santana, Jéssica Mirelly Almeida de (2018)
This study proposes a new methodology based on the detection by digital filming, using a webcam incorporated to a automatic batch-flow titrator (FBT-DM), to determine the total acidity of red wines. The chemical principle of titration is based on the presence of anthocyanins in the matrix of wines from the grape, which have different structures and colorations according to the acidity or alkalinity of the medium. In the titration implementation, the webcam records the digital film only during addition of the titrant in the mixing chamber, recording the color variations resulting from the acid-base reaction in the chamber interior. As the movie is recorded, it is decomposed into frames ordered sequentially at a constant rate of 30 frames per second (FPS). At the end of the titration, the software extracts the R, G, and B values of the resulting digital image sequence from the film to calculate the analytical response used in the construction of the titration curve. Only The R component was used as the analytical response for this purpose. The titration curves are obtained in real time by plotting the analytical signal (R-red channel) versus the titrant volume. The proposed method was used to analyze the samples of red wines and validated against potentiometric titration used as a reference method. It was found that there were no statistically significant differences between the results of the proposed method and the reference method by applying the paired t-test to the 95% confidence level. The FBT-DM titrator allow to analyse of 26 h-1 samples with relative standard deviation of less than 3.0% in the determination of the total acidity expressed as g.L-1 of tartaric acid. The sample and titrant reagent consumption was respectively 1,6 and 2,0 ml per analysis. The samples of red wines presented concentration between 10.5 and 14.9 g L-1 of tartaric acid.